EDUCATED WOMEN AND THEIR ROLE IN THE DEVELOPMENT OF SOCIETY - Kadamova Munisa Arslonbekovna; Shahlo Samanova (American Journals Publishing, 2024)
This article describes intelligent, intelligent and enlightened women in our society, and their lives and activities. Also, the role of enlightened women at all stages of the historical development of humanity, their influence on socio-economic processes, and their responsibility in educating the young generation are analyzed based on various literature.
Keywords: Family, society, woman, enlightenment, patriotism, humanity, intelligence, science, education, democracy, gender equality.